Biomechanical comparative analysis of effects of dynamic and rigid fusion on lumbar motion with different sagittal parameters: An in vitro study - Wang, Wei; Kong, Chao; Pan, Fumin; Wang, Yu; Wu, Xueqing; Pei, Baoqing; Lu, Shibao (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Although the management of the lumbar disease is highly dependent on the severity of the patient's condition, optimal surgical techniques to reduce the risk of adjacent degeneration disease (ADS) remain elusive. Based on in vitro biomechanical tests of the cadaver spine, this study aimed to comparatively analyze the kinematic responses of the spine with dynamic and rigid fixations (i.e., Coflex fixation and posterolateral fusion) after single-or double-level lumbar fusion in daily activities. Methods: Six human lumbar specimens (L1-S1) were selected for this experiment, and the sagittal parameters of each lumbar specimen were measured in the 3D model. The specimens were successively reconstructed into five groups of models: intact model, single-level L4-5 Coflex fixation model, single-level L4-5 Fusion (posterior pedicle screw fixation) model, double-level L4-5 Coflex+L5-S1 Fusion model; and double-level L4-5 Fusion+L5-S1 Fusion model. The pure moment was applied to the specimen model to simulate physiological activities in daily life through a custom-built robot testing device with an optical tracking system. Results: For single-level lumbar fusion, compared to the traditional Fusion fixation, the Coflex dynamic fixation mainly restricted the extension of L4-L5, partially retained the range of motion (ROM) of the L4-L5 segment, and reduced the motion compensation of the upper adjacent segment. For the double-level lumbar fixation, the ROM of adjacent segments in the Coflex+Fusion was significantly decreased compared to the Fusion+Fusion fixation, but there was no significant difference. In addition, PT was the only sagittal parameter of the preoperative lumbar associated with the ROM under extension loading. The Coflex fixation had little effect on the original sagittal alignment of the lumbar spine. Conclusion: The Coflex was an effective lumbar surgical technique with a less altering kinematic motion of the lumbar both at the index segment and adjacent segments. However, when the Coflex was combined with the fusion fixation, this ability to protect adjacent segments remained elusive in slowing the accelerated degradation of adjacent segments.